Correlation between angiographic findings and the ischaemia of head injury. Issue 2 (February 1978) - Macpherson, P; Graham, D I
Abstract : The carotid angiograms of 96 patients who had died from non-missile head injury were reviewed and assessed for evidence of arterial spasm, slowing of the cerebral circulation, and the presence of intracranial haemotoma. As bilateral angiography had been done in 44 cases the results are based on a correlation between the angiographic appearances and the presence or absence of ischaemic brain damage in the cortex of 140 cerebral hemispheres. There was a significant relationship between spasm alone, the presence of intracranial haematoma alone, or their combination, and ischaemic damage in the ipsilateral cortex. Apart from an association between the more severe grades of spasm and slowing of circulation in the group with ischaemia within arterial territories, there was none between slowing of the circulation or the combination of slowing with either spasm or haematoma and ischaemic brain damage.